PRODUCTION OF WEBSITE-BASED LEARNING MEDIA TO FACILITATE MASTERY OF PRECISION MECHANICAL MEASURING EQUIPMENT MATERIAL - Munazar, Muhamad Raehan; Daga, Mahpudin (Universitas Pendidikan Indonesia, 2024)
This research is motivated by students' difficulties when they want to learn independently to repeat the material of precision mechanical measuring instruments. This is because students do not have a handle on the material that can be accessed. Student difficulties need to be overcome by providing website-based learning media. The purpose of this research is to produce a website-based learning media that is feasible to use to facilitate students in mastering precision mechanical measuring instrument material and knowing the response of users. The trial was conducted in class X Automotive Engineering 2, totaling 31 students. The instrument used was a questionnaire. The results showed that website-based learning media is feasible to use to facilitate students in mastering precision mechanical measuring instruments, getting a very positive response from users, and website-based learning media can facilitate students in mastering precision mechanical measuring instruments.